The Thin Line (Book collections on Project MUSE., 2010)
Arja Salafranca is an accomplished writer, having twice won the Sanlam Literary Award in South Africa. The stories in her new book engage and reel in the reader on that 'thin line' from the start. The carefully drawn characters are haunting: Corinna trapped in her huge teenage body, Cleo in love with a married man after all these years, and poor skinny Mark, as he sees his love teeter away from him.'Ten Minutes to Hate' tells of an armed robbery in a packed theatre, and its effect, emotionally and psychologically, on two of the people involved. 'Collage' is the story of a possessive love so fierce, that only death can resolve it. Searingly honest, sometimes painfully so.